Critical analysis of the post-apartheid South African Government's discourse on infromation and communication technologies (ICTs), poverty and development - Moodley, Gunasagren (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (School of Public Management and Planning ))—University of Stellenbosch, 2005.